The role of angiotensin II and relaxin in vascular adaptation to pregnancy. Issue 4 (22nd September 2022) - Doan, Thu Ngoc Anh; Bianco-Miotto, Tina; Parry, Laura; Winter, Marnie
Abstract : In brief: There is a pregnancy-induced vasodilation of blood vessels, which is known to have a protective effect on cardiovascular function and can be maintained postpartum. This review outlines the cardiovascular changes that occur in a healthy human and rodent pregnancy, as well as different pathways that are activated by angiotensin II and relaxin that result in blood vessel dilation. Abstract: During pregnancy, systemic and uteroplacental blood flow increase to ensure an adequate blood supply that carries oxygen and nutrients from the mother to the fetus. This results in changes to the function of the maternal cardiovascular system. There is also a pregnancy-induced vasodilation of blood vessels, which is known to have a protective effect on cardiovascular health/function. Additionally, there is evidence that the effects of maternal vascular vasodilation are maintained post-partum, which may reduce the risk of developing high blood pressure in the next pregnancy and reduce cardiovascular risk later in life. At both non-pregnant and pregnant stages, vascular endothelial cells produce a number of vasodilators and vasoconstrictors, which transduce signals to the contractile vascular smooth muscle cells to control the dilation and constriction of blood vessels. These vascular cells are also targets of other vasoactive factors, including angiotensin II (Ang II) and relaxin. The binding of Ang II to its receptors activates different pathways to regulate the blood vessel vasoconstriction/vasodilation, and relaxin can interact with some of these pathways to induce vasodilation. Based on the available literature, this review outlines the cardiovascular changes that occur in a healthy human pregnancy, supplemented by studies in rodents. A specific focus is placed on vasodilation of blood vessels during pregnancy; the role of endothelial cells and endothelium-derived vasodilators will also be discussed. Additionally, different pathways that are activated by Ang II and relaxin that result in blood vessel dilation will also be reviewed.